Patriarchy in the Heritage of Bima Muslim Society: A Correlation between the Quran, Human Rights and Customs - ., Zuhrah; Handayani, I Gusti Ayu Ketut Rachmi; Harahap, Burhanuddin (Journal of Ecohumanism, 2024)
The Quran and Human Rights in general do not recognize the term patriarchy, either in the family system, roles or inheritance distribution specifically. But in the construction of human culture, classifying family forms, roles and inheritance divisions in the form of patriarchy. The division of inheritance in Islam is bilateral, in line with the Quran and human rights. However, the practice that occurs in Bima Muslim society is patriarchal, where inheritance takes precedence for men so that it is contrary to the Qur'anic commandments and human rights which have the purpose and principle of no discrimination between men and women. The practice according to the Bima Muslim community has been based on the Quran and is accustomed for generations to the next generation. This socio-legal research is conducted using qualitative methodology, and data analysis is done through critical analysis. This article significantly concludes that the pattern of inheritance distribution in Bima Muslim society is a patriarchal model. This practice violates the provisions of the Quran and the nawacita of human rights. Therefore, it is recommended that there should be socialization related to the rules of distribution of Islamic inheritance to the Bima Muslim community so that it is not understood based on the mindset of the community.